2020
DOI: 10.3390/cancers12030539
|View full text |Cite|
|
Sign up to set email alerts
|

Enhanced CXCR4 Expression Associates with Increased Gene Body 5-Hydroxymethylcytosine Modification but not Decreased Promoter Methylation in Colorectal Cancer

Abstract: In colorectal cancer (CRC), upregulation of the C-X-C motif chemokine receptor 4 (CXCR4) is correlated with metastasis and poor prognosis, highlighting the need to further elucidate CXCR4’s regulation in CRC. For the first time, DNA methylation and 5-hydroxymethylcytosine aberrations were investigated to better understand the epigenetic regulation of CXCR4 in CRC. CXCR4 expression levels were measured using qPCR and immunoblotting in normal colon tissues, primary colon cancer tissues and CRC cell lines. Public… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 67 publications
0
9
0
Order By: Relevance
“…CXCR4 expression and signaling is regulated through a variety of mechanisms. At a transcriptional level, CXCR4 expression may be modified through DNA methylation, directly activated by multiple transcription factors, and impacted by a range of physiologic stimuli ( 19 , 36 ). Protein expression may be impacted by tyrosine sulfation or glycosylation or modified by oligomerization.…”
Section: Discussionmentioning
confidence: 99%
“…CXCR4 expression and signaling is regulated through a variety of mechanisms. At a transcriptional level, CXCR4 expression may be modified through DNA methylation, directly activated by multiple transcription factors, and impacted by a range of physiologic stimuli ( 19 , 36 ). Protein expression may be impacted by tyrosine sulfation or glycosylation or modified by oligomerization.…”
Section: Discussionmentioning
confidence: 99%
“…CRC is the result of multiple etiological effects, one of which is the assemblage of diverse genetic or epigenetic alterations and their complex connections (21)(22)(23). Accumulating evidence has demonstrated that lncRNAs have considerable biological roles by modulating gene expression at multiple levels in tumorigenesis and tumor progression (24), and lncRNAs also form the main part of the ceRNA network of CRC.…”
Section: Discussionmentioning
confidence: 99%
“…A recent work by Stuckel et al showed that the overexpression of CXCR4 in human CRCs is observed in both colonocytes and stromal cells. The authors found that this overexpression is not the result of hypermethylation of the CpG islands of the CXCR4 promoter but rather of an increase in 5-hydroxymethylcytosine (5hmC), a marker of active demethylation of a gene [ 183 ]; and in this case, the accumulation of 5hmC would reflect increased transcription of CXCR4 in the CRC [ 184 ]. This work complements other studies demonstrating the regulation of CXCR4 expression by epigenetic processes associated with genome methylation.…”
Section: Mechanisms Of Expression Regulationmentioning
confidence: 99%